2009
DOI: 10.1177/1470320309105199
|View full text |Cite
|
Sign up to set email alerts
|

Perindopril decreases P wave dispersion in patients with stage 1 hypertension

Abstract: Introduction. Angiotensin-converting enzyme inhibitors prevent atrial fibrillation episodes by effective control of blood pressure and improving electrical and structural remodelling in the atria. Increased P wave dispersion (PWD) is a non-invasive electrocardiographic marker for paroxysmal atrial fibrillation. The aim of the study was to evaluate the effect of perindopril treatment on PWD in hypertensive patients. Methods. Forty-eight hypertensive patients (mean age 57.4±11.8 years, 18 men) were included. Blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Ozben et al. 76 found decrease in Pd with blockade of renin-angiotensin-aldosterone system (RAAS) with perindopril in hypertensive population. Korkmaz et al.…”
Section: Clinical Use Of Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozben et al. 76 found decrease in Pd with blockade of renin-angiotensin-aldosterone system (RAAS) with perindopril in hypertensive population. Korkmaz et al.…”
Section: Clinical Use Of Pdmentioning
confidence: 99%
“…Korkmaz et al 33 showed that nebivolol treatment in hypertensive patients decreased maximum P-wave duration and Pd. Ozben et al 76 found decrease in Pd with blockade of renin-angiotensin-aldosterone system (RAAS) with perindopril in hypertensive population. Korkmaz et al 33 also showed decrease in Pd with blockade of RAAS with quinapril in hypertensives.…”
Section: Atrial Fibrillationmentioning
confidence: 99%